A relação entre inteligência emocional, personalidade e luto: Um estudo com mães enlutadas - Monteiro, Amanda Piovani (Universidade Federal de São Carlos, 2025)
This study aims to investigate how emotional intelligence and personality relate to the grieving process in mothers who have lost their children. Approximately 50 women over 18 years of age will participate in the research. Data collection will be carried out using structured questionnaires that will assess emotional intelligence (TOHE, QoRE, and QoE), personality (BFI), and grief (TRIG). The expected results indicate whether individuals with high levels of emotional intelligence exhibit better adaptive strategies, resulting in more effective grief coping. Furthermore, it is believed that certain personality traits, such as high conscientiousness and low neuroticism, are associated with a less intense and more adaptive grief experience. It is also predicted that the interaction between high emotional intelligence and positive personality traits (such as agreeableness and openness to experience) will lead to a healthier and less dysfunctional grief experience.
The relationship between emotional intelligence, personality, and grief: a study with bereaved mothers
Keywords: inteligência emocional; personalidade; luto; avaliação psicológica; testes informatizados; CIENCIAS HUMANAS::PSICOLOGIA::FUNDAMENTOS E MEDIDAS DA PSICOLOGIA::CONSTRUCAO E VALIDADE DE TESTES, ESCALAS E OUTRAS MEDIDAS PSICOLOGICAS; 3. Saúde e Bem-Estar